The Satisfaction Analysis of Bus Double Decker Passengers: A Case Bekasi-Semarang Route - Bagus Dewantoro, Rahman; Rifai, Andri Irfan; Akhir , Adinda Fajarika (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
Double-decker buses are the latest mode of public transportation that is one of the choices for travelers. Passenger satisfaction is the main thing, so this mode remains an option and increasingly provides a good level of service. This paper aims to analyze the level of importance and customer satisfaction. The method used is importance performance analysis using survey data with questionnaires. Data was obtained from passengers of the Bekasi-Semarang double-decker bus route, which was found directly at Bulak Kapal Bus Station. The results showed that most of the measured parameters had a high level of satisfaction. However, four parameters need more attention, one of which is the polite staff. The average importance level is 8.93, with a satisfaction rate of 8.78.